Dietary Corn Bran Altered the Diversity of Microbial Communities and Cytokine Production in Weaned Pigs - Liu, Ping; Zhao, Jinbiao; Wang, Wei; Guo, Pingting; Lu, Wenqing; Wang, Chunlin; Liu, Ling; Johnston, Lee J.; Zhao, Yuan; Wu, Xianhua; Xu, Chi; Zhang, Jie; et al. (Frontiers in Microbiology, 2018)
Corn bran has been used as an ingredient for pigs, but the underlying mechanisms that improve gut health is less clear. This study was conducted to investigate effects of dietary corn bran on growth performance, nutrient digestibility, plasma indices related to gut hormones and immunity, gut microbiota composition, and fermentation products in weaned pigs. A total of 60 weaned pigs were allocated to 2 dietary treatments, and piglets in each group received control (CON) diet or 5% corn bran (CB) diet for 28 d. Growth performance, nutrient digestibility, indices of gut hormones and immunity in plasma were evaluated. Microbiota composition in feces was determined using 16S rRNA amplicon sequencing, and fermentation products were measured by high-performance ion chromatography. The results showed that dietary CB did not affect growth performance, nutrient digestibility, gut hormones, or fermentation products in the trial (P > 0.05). There was an increased response to CB inclusion on interleukin-10 production (P < 0.05). On d 28, piglets fed dietary CB had a higher shannon index (P < 0.05). The population of the Firmicutes in CB treatment were decreased (P < 0.05), while the percentage of the Bacteroidetes were increased (P < 0.05). In particular, the populations of Eubacterium corprostanoligenes, Pevotella, and Fibrobacter related to polysaccharide fermentation of cereal bran were increased (P < 0.05). In conclusion, a post-weaning diet containing 5% CB increased intestinal microbial diversity, especially higher richness of fibrolytic bacteria, and promoted anti-inflammatory response to some extent in piglets, these changes should facilitate the adaptation of the digestive system of piglets in the subsequent growing phases.